Epochal Change and Second Modernity as a Sociocultural Manifestation of Managerialism (Global Journal of Human-Social Science, 2023)
This paper returns to the prevalent notion of an epochal change that transformed advanced societies towards the turn of the millennium Using the neutral term second modernity to capture this polyonymous phenomenon three of its constitutive cultural attributes are discussed uncertainty and insecurity immediacy and accelerating rates of change and the flattening of hierarchies and rigid organisations The paper first reviews the way these attributes and their consequences were analysed by proponents and opponents of a postmodern break with the past It is then shown that the new managerial discourse and practices which arose concurrently with all these transformations both endorsed and propelled them At the same time these processes their effects and interpretations all increased the importance and social standing of management in organisations and society at large They also promoted the ethical and ideological foundation of the social ascendency of managers Together this lends support to perceiving the rise of second modernity as the sociocultural manifestation of the new social order of managerialism